Implicit Assessment and Argumentation - E. R. Ioanesyan (Научный диалог, 2020)
The article is devoted to the problem of implicitness. As an object of study, sentences with a conjunction but, sentences with a conjunction and , sentences with a quantifier word any (a quantifier of generality) and sentences with a construction of the form not important P (X ) (modus of indifference) were selected. The types of evaluations that may be implicitly contained in such sentences are analyzed. The study showed that sentences with a conjunction but as well as sentences with a conjunction and often contain a negative or positive implicit assessment of one of the participants in the situation described in the proposal. It was also established that, in contrast to the generality quantifier in logic - ⱯxP( x ), which means that “property P takes place for all x”, in the language the quantifier words and the words of the mode of indifference can focus not on the whole scale X, but on the extreme points of this scale. The indicated features of the quantifier of any of the constructions not important P(X) determines the type of assessment that can be implicitly contained in statements with these units, and the features of their functioning in the argumentative discourse. The relevance of the study is aimed at identifying implicit meanings. In the context of modern linguistics, implicitness is the subject of interest of many researchers.